ANALISIS RUANG EKOLOGIS SISTEM PERIKANAN BERKELANJUTAN DESA OLUHUTA KECAMATAN KABILA BONE KABUPATEN BONE BOLANGO - Djau, Mohamad Sayuti; Achmad, Dewi Shinta (AKADEMIKA, 2013)
Population growth, the expansion of settlements and the increasing activities of fishing either directly or indirectly, in Oluhuta region caused the ecological balance. The aim of this research was firstly to analysed the sustainability of space for metabolism of social ecological fishery utilization. Secondly, to evaluate the sustainability of fisheries in the region using the ecological footprint approach. The result showed that the sustainability of space for the metabolism of ecological social fishery system in this area is 1.96 km2/capita which is accepted condition. Sustainable fisheries management should be oriented towards the problem using scientific methods based on the physical, biological, social, economic and cultural communities